Population-level impact of COVID-19 on thyroid function tests: Results from a repeated cross-sectional study - Gabriel Berkebile; Françoise Barbé; Catherine Malaplate; Lauriane Le Collen; Jean-Louis Guéant; Marc Klein; Abderrahim Oussalah (Journal of Infection and Public Health)
Purpose: Reports have highlighted thyroid abnormalities, including subacute thyroiditis and thyrotoxicosis, in COVID-19 patients, with a potential link between thyroid dysfunction and disease severity. However, population-level studies on COVID-19’s impact on thyroid hormone levels are limited. We aimed to assess the impact of the COVID-19 pandemic on thyroid function tests at the population level. Methods: We conducted a repeated cross-sectional study on consecutive patients who underwent thyroid function tests between March 1 and April 15, 2020, during the first wave of COVID-19 in northeastern France, and compared the results with those from the same period in 2018 and 2019. Results: The study analyzed 3968 tests, including 1534 in 2018, 1547 in 2019, and 887 in 2020. Patients tested in the first wave of COVID-19 had significantly lower TSH and FT3 levels and higher FT4 levels than those in reference periods. On ROC analysis, the optimal thresholds for FT3 and FT4 were ≤ 4.5 pmol/L and > 12 pmol/L, respectively. On multivariable analysis, FT3 ≤ 4.5 pmol/L and FT4 > 12 pmol/L were independently associated with the first wave of COVID-19. The proportion of subjects with concurrent changes in FT3 and FT4 levels was significantly higher in 2020 than in the reference periods, with an odds ratio of 3.62 (95 % CI, 2.77–4.73). A phenome-wide association study of 128 clinical and biological predictors identified an independent association between a low FT3/FT4 ratio and COVID-19, hypertension, or amiodarone therapy, suggesting the contribution of euthyroid sick syndrome to this presentation. This association remained significant after adjustment for potential confounders such as thyroid disease, steroids, and iodinated contrast injection. Conclusion: These findings suggest that COVID-19 is associated with significant population-level variation in thyroid function tests, which may have implications for managing COVID-19 patients.